The Contribution of Plasma and Brain Vitamin C on Age and Gender-Related Cognitive Differences: A Mini-Review of the Literature - Travica, Nikolaj; Ried, Karin; Hudson, Irene; Sali, Avni; Scholey, Andrew; Pipingas, Andrew (Frontiers in Integrative Neuroscience, 2020)
There is increasing evidence that sex differences in the brain may contribute to gender related behavioral differences, including cognitive function. Literature has revealed gender dimorphisms in cognitive function between males and females. Additionally, a number of risk factors associated with cognitive decline depend on chronological age. It is well recognized that the process of aging is associated with a decline in cognitive ability and brain function. Various explanations may account for these gender related cognitive differences and age associated cognitive changes. Recent investigations have highlighted the importance of vitamin C in maintaining brain health and its association with cognitive function in both cognitively intact and impaired cohorts. The present review explores previous literature which has evaluated differences in plasma/brain vitamin C between genders and during aging. It then assesses whether these age and gender related differences may affect the relationship between plasma/brain vitamin C and cognition. The purpose of this review was to examine the evidence for a link between plasma/brain vitamin C and cognition and the impact of gender and age on this relationship. Epidemiological studies have frequently shown higher vitamin C plasma concentrations in women. Similarly, aging has been systematically associated with reductions in plasma vitamin C levels. A range of animal studies have demonstrated potential gender and age related differences in vitamin C brain distribution and utilization. The reviewed literature suggests that gender differences in plasma and brain vitamin C may potentially contribute to differences in gender associated cognitive ability, particularly while females are pre-menopausal. Additionally, we can propose that age associated differences in plasma and brain vitamin C may be potentially linked to age associated cognitive differences, with older cohorts appearing more vulnerable to experience declines in plasma vitamin C concentrations alongside compromised vitamin C brain regulation. This review encourages future investigations to take into account both gender and age when assessing the link between plasma vitamin C concentrations and cognitive function. Further large scale investigations are required to assess whether differences in cognitive function between genders and age groups may be causally attributed to plasma vitamin C status and brain distribution and utilization.